2020
DOI: 10.3390/ijms21061960
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Cyclin-Dependent Kinases in Cell-Cycle Progression and Therapeutic Strategies in Human Breast Cancer

Abstract: Cyclin-dependent kinases (CDKs) are serine/threonine kinases whose catalytic activities are regulated by interactions with cyclins and CDK inhibitors (CKIs). CDKs are key regulatory enzymes involved in cell proliferation through regulating cell-cycle checkpoints and transcriptional events in response to extracellular and intracellular signals. Not surprisingly, the dysregulation of CDKs is a hallmark of cancers, and inhibition of specific members is considered an attractive target in cancer therapy. In breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
261
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(269 citation statements)
references
References 181 publications
5
261
0
3
Order By: Relevance
“…In particular, CDK2 is listed as one of the top suggested kinases. It is interesting to note that the suggestion of CDK2 as a potential target is perfectly tuned with its known expression in breast cancer 37 , and with the obtained results from the cell cycle analysis, as the role of CDK2 in the cell cycle is well-established 3 . Accordingly, a molecular docking work was conducted in order to examine the plausible binding modes and interactions of the target pyridazines 11a-r within the active site of CDK2.…”
Section: In Silico Target Predictionmentioning
confidence: 85%
“…In particular, CDK2 is listed as one of the top suggested kinases. It is interesting to note that the suggestion of CDK2 as a potential target is perfectly tuned with its known expression in breast cancer 37 , and with the obtained results from the cell cycle analysis, as the role of CDK2 in the cell cycle is well-established 3 . Accordingly, a molecular docking work was conducted in order to examine the plausible binding modes and interactions of the target pyridazines 11a-r within the active site of CDK2.…”
Section: In Silico Target Predictionmentioning
confidence: 85%
“…The downregulation of CDK1 has been associated with breast cancer by Lie Ding et al [28]. Moreover, Lie Ding et al [28] also reported that breast cancer patients with overexpression of CDK1 and CDK2 had signi cantly poorer OS compared to those with low CDK1 and CDK2 expression. Similar role of CDKs has also been reported in renal cell carcinoma [29].…”
Section: Discussionmentioning
confidence: 98%
“…The cell cycle dysregulation is the major event that occurs in cancer cells [26] and Cyclin-dependent kinases (CDKs) are the well-known proteins involved in the regulation of cell cycle [27]. The downregulation of CDK1 has been associated with breast cancer by Lie Ding et al [28]. Moreover, Lie Ding et al [28] also reported that breast cancer patients with overexpression of CDK1 and CDK2 had signi cantly poorer OS compared to those with low CDK1 and CDK2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP-competitive inhibitor, dinaciclib, exhibited IC 50 sub 4 nM against a broad spectrum of CDKs (1, 2, 5, and 9) and RB phosphorylation in BC cell lines, simultaneously with induction of apoptosis, all of which was better compared to flavopiridol. It was also reported that the combination of dinaciclib with an anthracycline showed synergism in BC cell lines [ 38 ]. It also showed encouraging efficacy, safety, and tolerability profiles as a monotherapy in a clinical trial phase II for advanced BC, which involved ER + /Her2 - patients.…”
Section: Discussionmentioning
confidence: 99%